2018
DOI: 10.3390/app8030434
|View full text |Cite
|
Sign up to set email alerts
|

Study on Actuator Line Modeling of Two NREL 5-MW Wind Turbine Wakes

Abstract: Abstract:The wind turbine wakes impact the efficiency and lifespan of the wind farm. Therefore, to improve the wind plant performance, research on wind plant control is essential. The actuator line model (ALM) is proposed to simulate the wind turbine efficiently. This research investigates the National Renewable Energy Laboratory 5 Million Watts (NREL 5-MW) wind turbine wakes with Open Field Operation and Manipulation (OpenFOAM) using ALM. Firstly, a single NREL 5-MW turbine is simulated. The comparison of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…It is to be noted that there is no tip-loss correction in the ALM-LBM-LES model. Yu et al [35] showed that adding a tip-loss correction when modeling a horizontal axis wind turbine can reduce the error of the predicted power. It could be an interesting addition to the ALM-LBM-LES model.…”
Section: Discussionmentioning
confidence: 99%
“…It is to be noted that there is no tip-loss correction in the ALM-LBM-LES model. Yu et al [35] showed that adding a tip-loss correction when modeling a horizontal axis wind turbine can reduce the error of the predicted power. It could be an interesting addition to the ALM-LBM-LES model.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation physical domains used in this paper are the same as Yu et al [28]. Their three-dimensional sketches are shown in Figures 6 and 7.…”
Section: Computational Wind Turbine Modelmentioning
confidence: 99%
“…To be exact, the shaft tilt angle is considered in the structural part, which will make the external force of blade increased because of the gravity component. The simulation physical domains used in this paper are the same as Yu et al [28]. Their three-dimensional sketches are shown in Figures 6 and 7.…”
Section: Computational Wind Turbine Modelmentioning
confidence: 99%
See 2 more Smart Citations